2017
DOI: 10.1177/1477153517708597
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life cycle assessment of LED lighting products

Abstract: LED lighting products used in lighting applications and their subsequent environmental impact are growing rapidly. However, there are no in-depth updated studies that show how to assess and compare them for eco-design purposes. This research aims to add insights in this area to inform eco-design by assessing and comparing the environmental impact of a new LED eco-lighting product with an existing LED lighting product. A cradle to grave Life Cycle Assessment (LCA) was conducted using ReCiPe Midpoint and Endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 9 publications
(20 reference statements)
3
19
0
3
Order By: Relevance
“…3. The results of the Tähkämö et al (2013) study were confirmed in a more recent comparative LCA for LED lighting products, which also considered an even shorter scenario of 1000 hours lifetime (compared to 15,000 and 40,000 hours lifetimes) (Casamayor et al 2017). Not only did the assumption of shorter lifetimes result in significantly higher impacts of both LED products considered, but it also resulted in the main environmental impacts coming from the manufacturing, rather than the use phase.…”
Section: Lca Approachsupporting
confidence: 71%
See 1 more Smart Citation
“…3. The results of the Tähkämö et al (2013) study were confirmed in a more recent comparative LCA for LED lighting products, which also considered an even shorter scenario of 1000 hours lifetime (compared to 15,000 and 40,000 hours lifetimes) (Casamayor et al 2017). Not only did the assumption of shorter lifetimes result in significantly higher impacts of both LED products considered, but it also resulted in the main environmental impacts coming from the manufacturing, rather than the use phase.…”
Section: Lca Approachsupporting
confidence: 71%
“…10 A more recent LCA also confirmed the findings of greater overall environmental impacts associated with shorter lifespans for LED lamps (see Casamayor et al 2017).…”
Section: Lca Approachsupporting
confidence: 65%
“…Forexample,reliance on rare-earth-based phosphors puts ah igh burden, since production costs are high, supply and sustainability are low, ecological impact related to mining and shipping of raw materials is high, and recycling protocols are still nonexistent. [9][10][11] In addition, potential health risks related to the pronounced blue component of the WILED emission that may affect the bodysb iological clock-that is,t he circadian rhythm-are under hot debate. [12][13][14][15][16] Over the last decades,f luorescent proteins (FPs) have been extensively employed for imaging and tracing in cell biology and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Zudem werden mçgliche gesundheitliche Risiken, die aus der ausgeprägten Blau-Komponente der WILED-Emission resultieren und die die biologische Uhr des Menschen beeinträchtigen kçnnten, heiß diskutiert. [9][10][11] Zudem werden mçgliche gesundheitliche Risiken, die aus der ausgeprägten Blau-Komponente der WILED-Emission resultieren und die die biologische Uhr des Menschen beeinträchtigen kçnnten, heiß diskutiert.…”
Section: Introductionunclassified
“…Zum Beispiel bringt die Nutzung von Phosphoren auf Seltenerd-Basis verschiedene Probleme mit sich:D ie Produktionskosten sind hoch, die Verfügbarkeit und die Nachhaltigkeit sind gering, die Umweltbelastung durch Gewinnung und Tr ansport der Rohstoffe ist hoch, und bislang fehlen entsprechende Recycling-Verfahren. [9][10][11] Zudem werden mçgliche gesundheitliche Risiken, die aus der ausgeprägten Blau-Komponente der WILED-Emission resultieren und die die biologische Uhr des Menschen beeinträchtigen kçnnten, heiß diskutiert. [12][13][14][15][16] Die genannten Probleme führten zur Entwicklung von organisch-anorganischen Hybrid-WLED (WHLED), um die Vorteile beider Ansätze in einem einzigen Bauelement zu vereinen (Abbildung 1).…”
Section: Introductionunclassified